2016
DOI: 10.1590/1981-863720160003000052985
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of photodynamic therapy on Candida species isolated from oral samples of children exposed and not exposed to HIV

Abstract: Objective: Identify yeast species isolated from unexposed, exposed and HIV-carrier children, and verify the effectiveness of low power laser photodynamic therapy (PDT) on the yeasts species belonging to the Candida genus. Methods: Fifty children assisted by the Public Health Program of the city of Vitória da Conquista, Bahia, were selected and divided into three groups: unexposed to HIV, exposed to HIV during pregnancy, and HIV-carrier. Saliva samples were collected in a disposable sterile universal container… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(48 reference statements)
0
2
0
1
Order By: Relevance
“…The oxygen molecules that receive the energy undergo a series of photochemical reactions to produce singlet oxygen and a variety of reactive oxygen species with strong oxidation [4]. Studies have shown that PDT-mediated treatment of periodontal disease can eliminate plaque formation without involving normal periodontal mucosal tissue [5]. It has also been reported that by culturing Streptococcus mutans in vitro and pretreating them with PDT method, the growth and proliferation of bacteria can be effectively inhibited [6].…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen molecules that receive the energy undergo a series of photochemical reactions to produce singlet oxygen and a variety of reactive oxygen species with strong oxidation [4]. Studies have shown that PDT-mediated treatment of periodontal disease can eliminate plaque formation without involving normal periodontal mucosal tissue [5]. It has also been reported that by culturing Streptococcus mutans in vitro and pretreating them with PDT method, the growth and proliferation of bacteria can be effectively inhibited [6].…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento das infecções fúngicas com agentes fotossensibilizantes têm ganhado atenção como uma alternativa viável aos tratamentos convencionais, visto que a TFD com o laser de baixa potência é eficaz na inativação dos fungos 22 .…”
Section: Discussionunclassified
“…Most previous studies have evaluated the effects of photodynamic therapy on C. albicans in animal models or in vitro. [9][10][11][12][13][14][15] Since there is no study on the effectiveness of photodynamic therapy and laser therapy in eradicating resistant Candida species, including C. glabrata, C. tropicalis, and C. krusei, this study aimed to investigate the effects of photodynamic therapy on the growth of these resistant Candida species in vitro.…”
Section: Introductionmentioning
confidence: 99%